Kejahatan Siber di Indonesia Pada Masa Pandemi Covid-19 Ancaman dan Pencegahan dalam Kajian Intelijen Strategis - Christanto Paulus Rumapea; Maria Puspitasari (Syntax Literate, 2023)
This research is motivated by an increase in cybercrime cases in recent years, especially during the COVID-19 pandemic. These various forms of cybercrime pose a real threat to Indonesia's national security. This research uses the theory / concept of strategic intelligence and black swan (black swan) as a basis for thinking. Using descriptive qualitative methods with literature study data collection techniques by utilizing previous research and institutional data as a basis for conducting analysis. The results show that cybercrime is a major threat to Indonesia's national resilience. The COVID-19 pandemic is an indirect catalyst for the increasing number of cybercrime cases where people are increasingly "urged" to better adapt online activities so as to enable many cybercrime crimes. The threat of this crime is very risky to public security such as opinion gathering that has the potential to divide the community and decrease trust in the government / certain parties In addition, data theft and online fraud can cause economic / financial losses, to risk public data security. To detect threats early, interagency cooperation by utilizing existing intelligence resources is needed. However, obstacles were found in terms of coordination and cooperation between institutions that have not been maximized, so a strategic policy is needed in the concept that regulates collaboration between institutions